Menggeliatnya Bisnis Dan Investasi Properti Di Surakarta - Paningrum, Destina (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2013)
In  this  moment  , property  investment  be  the  favourite for businessman  as  considered safelyand promising for bright prospects in Surakarta. Moreover, the property segment in Indonesia  highly  open  wide,  both  for  Investment  and  Business.  Shopping  center,  home property that  can  be  a  golden  opportunity  to  invest  in  lucrative property.  The demographic layout is located in the city of Surakarta, Central Java province , Indonesia. The population of 503.421 inhabitants (2010 ) and the density of 13.636 inhabitants / km2 Where  size  44 km2  city  that  around  Karanganyar  And  Boyolali  in  northside, Karanganyar  and  Sukoharjo  in  next  east  and  west,  and  Sukoharjo  in  the  south,  Its Business  Property  can  be  highly  profitable,  because  so  many  newcomers  settled  in Surakarta.  The  Business  is  growing. In Surakarta malls  or  shopping  center  which  also adds to the advance of property in Surakarta.Keywords :Property Investement, Demography of Surakarta, Profit and Loss Business of Property in Surakarta